Inclusión de cáscara de maracuyá (Passiflora eduilis sims) en las características microbianas fermentación del ensilaje de maiz forrajero (Zea mays) en el cantón Mocache - Viri Orellana, Jessica Magaly (2019)
The objective of the research was to determine the microbiological and fermentative characteristics of forage maize silage (Zea mays) with inclusion levels of passion fruit peel (Passiflora edulis Sims). It was executed in the Rumiology Laboratory in the experimental farm "La María", in the State Technical University of Quevedo, located at Km 7 of the Quevedo - El Empalme road, San Felipe, Mocache. A Completely Random Design (CRD) was used, with five treatments and five replications: T1 with 100% fodder corn (control); T2 75% fodder corn including 25% passion fruit husk; T3 50% fodder corn including 50% passion fruit peel; T4 25% fodder corn including 75% passion fruit peel and T5 100% passion fruit husk. The variables of lactic acid bacteria, fungus, yeasts and aerobic stability (pH and Temperature) were evaluated. Upon analyzing the growth of the lactic acid bacteria in the micro silos of corn, there was no statistical difference between evaluated treatments. Fungus growth did not show a difference between treatments neither Meanwhile, the growth of yeast was significant where the T5 presented the least growth of fungus at 7.46 UFC mL-6. The differentiations of temperature in the different treatments at different times showed that the treatment with the highest temperature was T1 at 120 hours with 28.4 degrees C, whereas, the rest of the treatments sustained their temperature between 26 and 27 degrees, where the bacteria population grew the most. In the same case as temperature, the pH was tested at 24 hour intervals and the last test was at 144 hours (7 days), obtaining the changes in the pH in each different treatment according to the time. The treatments with and without the inclusion of passion fruit husk had a pH of 5 from 24 hours to 96 hours, indicating acidity in the treatments. However, at 144 hours the T1, T2, T3, T4 and T5 reached a pH range of 7.43 to 7.83, which demonstrates alkalinity in all of the treatments. Keywords: aerobic stability, silage, passion fruit, microbiological characteristics